Penerapan Algoritma Random Walk Untuk Procedural Map Pada Game “The Last Hope” 2D - Muhammad Ijai; Arbansyah, Arbansyah; Suryawan, Sayekhti Harits (Universitas Muhammadiyah Riau, 2023)
Games are activities that aim to provide fun and offer certain rules and challenges, with the aim of creating a dynamic and interesting gaming experience. This research aims to overcome the problem of repetition in making maps in the game